RANCANG BANGUN SIMULASI PERGERAKAN HIGH LIFT DEVICE PADA PESAWAT - lalu giat juangsa putra; James Siregar; Dedy Syarif Qusyairi (Politeknik Negeri Batam, 2020)
The most high lift device modifying, for small airplanes and large, is the wing flap. Flaps can be installed on the leading edge or trailing edge (only for large airplane) aircraft. To make a simulator, the design and also the drive system are needed which will form the movement as in the real flap. As a driving mode, the system which designed on this flap simulator will use an electronic system. By using a servo motor as a drive and Arduino as a microcontroller that will be programmed according to the planned movement. The flap simulator can produce angles formed on servo motors such as 5º, 14º, 19º, 25º and 30º its moving flaps on flap level 0, 1, 2, 3 and 4 in extend and retract movement modes.